Diagnostic, Therapeutic and Monitoring Approach in Suspected Neurosyphilis: Proposal for a Clinical Guideline - Martins, Bárbara (2024)
This clinical guideline was designed to serve as a hospital guide in the diagnostic, therapeutic, and monitoring approach to neurosyphilis, considering whether there is positivity or not for the human immunodeficiency virus. Syphilis is a sexually transmitted notifiable disease, known as the great imitator. In around 30% of cases of untreated disease, there is a persistent central nervous system infection. Neurosyphilis is a severe and progressive form of syphilis, which can occur at any stage of the disease, with frequent delays in diagnosis and treatment. It is classified as early neurosyphilis (syphilitic meningitis, meningovascular neurosyphilis, or syphilitic gummas) and late neurosyphilis (syphilitic gummas, general paresis, or tabes dorsalis). The importance of lumbar puncture lies not only in its diagnostic value but also in evaluating the effectiveness of treatment. The treatment of this disease in all stages consists of parenteral penicillin. With this guideline, our aim is to facilitate clinical decision-making in cases of suspected neurosyphilis through a systematized, individualized, and multidisciplinary approach.